Characterization of breast tumors with unbalanced levels of progesterone receptor isoforms: a proteomic approach - Elia, Andres Maximiliano (2022)
It is well established that progesterone receptors (PR) play a relevant role in breast carcinogenesis and that a misbalanced expression of PR isoforms differentially affects breast cancer progressionand antiprogestin treatment responsiveness.Moreover, we have shown, in preclinical and clinical studies, that mifepristone exerts antiproliferative effects in tumors expressing higher levels of PR isoform A (PRA) than B (PRB), named PRA-H, suggesting the necessity to develop methods to identify these patients using non-invasive technologies. Our aim was to compare the proteome profile of PRA-H breast carcinomas with those with the opposite ratio (PRB-H). Nuclear and cytosolic protein fractions were obtained from 18 breast cancer samples classified as PRA-H or PRB-H and were studied by LC-MS/MS (UltiMate 3000 LC system - Q Exactive HF-X mass spectrometer - Thermo). We observed 289 differentially regulated proteins in cytosol (164 down and 125 up) and 301 in nuclear extracts (131 down and 170 up; logFC > 1, pval < 0.05) from both groups. Enrichment analysis showed biological processes related to intracellular transport (FDR = 9.58e-08), metabolic (FDR = 0.0028) and actin filament-based processes (FDR = 1.79e-05) in PRB-H tumors; while in PRA-H tumors, pathways related to oxoacid metabolic (FDR = 0.0015), immune effector (FDR = 1.59e-08) and electron transport chain (FDR = 3.35e-06) processes were enriched. Finally, using the differentially expressed proteins, we studied those that might be secreted. Among them, we found CPB1, whose differential mRNA expression has already been reported in a similar setting in previous assays. This study underscores the biological differences between PRA-H and PRB-H breast carcinomas and provides candidates that might be used as surrogate markers in plasma to identify patients that may benefit from an antiprogestin treatment.